Análise da influência de variantes do método de solução de escoamentos utilizando os métodos de elementos finitos com compressibilidade artificial e pseudo-características - Oliveira, Marcos Paulo de Carvalho [UNESP] (2007)
The development of numerical models for fluid flow simulation occurred at many aspects: since coupling methods between pressures and velocities until stabilization techniques. In this context, this work intends to implement and evaluate one algorithm behavior, the CBS, used in a simulation of incompressible and isothermal flows. This work also uses the explicit and semi-implicit methods of the time discretization scheme and some others changes in space discretization and stabilization terms for tests with algorithm. The discretization technique used is the finite element method with the mesh formed by bilinear elements. The algorithm's changes were evaluated using results for several Reynold's number in a classic problem: the lid-driven cavity. All the changes in solution algorithm with the used mesh show good agreement with other results from bibliography. It was verified too, that the omission of characteristics term didn't present significant differences in results with Reynold's number tested. It was observed yet that the solution code using the semi-implicit method converges with less time steps than the explicit one.